SOBRESSEMEADURA DE ESPÉCIES HIBERNAIS EM TIFTON 85 SOB PASTEJO: ESTABELECIMENTO - Krahn, Jaqueline R. T.; Maixner, Adriano R.; Uhde, Leonir T.; Londero, Ana L.; Dreilich, Nailene D.; Zorzella, Marinei D. (Salão do Conhecimento, 2013)
Resumo